SOSIALISASI STRATEGI PEMANFAATAN RUANG RUMAH KECIL DIPERUMAHAN CITRA SMALL TOWN MERAUKE - Yashinta Irma Pratami Hematang; Anton Topan (Musamus University, 2021)
The small type of housing, namely type 36, is mostly built in housing in addition to meetingthe needs of 1000 houses for the Jokowi Program, as well as targeting the middle to lowereconomic community. This phenomenon is also starting to bloom in Merauke. But behindthat, the community needs a design strategy to manage these small types of houses.Therefore, this service activity is carried out with the aim of providing education to thepublic through a socialization about this strategy. Community service partners are residentsof the Citra Small Town Merauke housing estate. The method of socialization is bypresenting the material directly to the homeowners. After that, a question and answerdiscussion session is opened and ends with the delivery of impressions and messages fromthe Head of Housing of Citra Small Town and representatives of socialization participants.The result of this activity is the acquisition of knowledge for the occupants of the house,especially in terms of the development of small type houses in the future as well as obtainingoutputs from scientific journal publications, photo documentation, and video testimonials ofactivities